Okvirna konvencija Sveta Evrope za zaščito narodnih manjšin - Klopčič, Vera (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 1994)
In January 1994 a special committee was founded within the Council of Europe. Its task was to prepare, in accordance with the already adopted international documents and the CSCE principles, a draft convention and a preliminary text of an additional protocol to the European Convention on Human Rights. The Convention is the first overall and compulsory international legal document on national minority protection. Its signatories have assumed the obligation to create adequate conditions for the expressing, preserving and promoting of national minority identity, as well as to provide for an atmosphere of tolerance and dialogue, which is to allow for cultural diversity to become an enrichment of every society.
Keywords: mednarodne konvencije; narodne manjšine; Svet Evrope